Upconversion luminescence properties of NaBi(MoO4)2:Ln3+, Yb3+ (Ln = Er, Ho) nanomaterials synthesized at room temperature. Issue 11 (1st August 2020) - Pushpendra; Kunchala, Ravi K.; Kalia, Rimple; Naidu, Boddu S.
Abstract: Studies on lanthanide ions doped upconversion nanomaterials are increasing exponentially due to their widespread applications in various fields such as diagnosis, therapy, bio-imaging, anti-counterfeiting, photocatalysis, solar cells and sensors, etc. Here, we are reporting upconversion luminescence properties of NaBi(MoO4 )2 :Ln 3+, Yb 3+ (Ln = Er, Ho) nanomaterials synthesized at room temperature by simple co-precipitation method. Diffraction and spectroscopic studies revealed that these nanomaterials are effectively doped with Ln 3+ ions in the scheelite lattice. DR UV–vis spectra of these materials exhibit two broad bands in the range of 200–350 nm correspond to MoO4 2− charge transfer, s-p transition of Bi 3+ ions and sharp peaks due to f-f transition of Ln 3+ ions. Upconversion luminescence properties of these nanomaterials are investigated under 980 nm excitation. Doping concentration of Er 3+ and Yb 3+ ions is optimized to obtain best upconversion photoluminescence in NaBi(MoO4 )2 nanomaterials and is found to be 5, 10 mol % for Er 3+, Yb 3+, respectively. NaBi(MoO4 )2 nanomaterials co-doped with Er 3+, Yb 3+ exhibit strong green upconversion luminescence, whereas Ho 3+, Yb 3+ co-doped materials show strong red emission. Power dependent photoluminescence studies demonstrate that emission intensity increases with increasing pump power. Fluorescence intensity ratio (FIR) and population redistribution ability (PRA) of 2 H11/2  →  4 I15/2, 4 S3/2  →  4 I15/2 transitions of Er 3+ increases with increasing the Yb 3+ concentration. Also, these values increase linearly with increasing the pump power up to 2 W. It reveal that these thermally coupled energy levels are effectively redistributed in co-doped samples due to local heating caused by Yb 3+ . Graphical abstract: Image 1